Exploring coping strategies among caregivers of children who have survived paediatric cancer in Jordan - Noor Ismael; Ala'a Jaber; Somaya Malkawi; Sherin Al Awady; Taleb Ismael (BMJ Publishing Group, 2024)
Objective To explore the coping strategies of caregivers of children who have survived paediatric cancer in Jordan.Materials and methods This study used a cross-sectional survey design and convenient sampling. The sample included 102 caregivers of children who have survived cancer, and outcome measures included the Arabic-translated Brief COPE, and caregiver and child demographic and condition questionnaire. Data analyses included descriptive statistics, analysis of frequencies, Spearman-rank order correlations and linear regression.Results Caregivers most frequently used religion coping (mean=6.42, SD=1.85), followed by acceptance (mean=5.95, SD=1.96) and planning (mean=5.05, SD=1.94). The least used coping strategies were humour (mean=2.98, SD=1.24) and behavioural disengagement as coping strategies (mean=3.01, SD=1.42). Having a female child predicted more self-distraction utilisation (β=0.265, p=0.007).Conclusion Caregivers of children who have survived cancer in Jordan frequently use passive coping strategies like religion and acceptance coping to overcome daily life stressors. Caregivers might benefit from psychosocial occupational therapy interventions to support their engagement in more active or problem-focused coping strategies.